2016
DOI: 10.1016/j.biopsycho.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological correlates of face-evoked person knowledge

Abstract: Face recognition includes identifying a face as perceptually familiar and recollecting biographical information, or person-knowledge, associated with the face. The majority of studies examining the neural basis of face recognition have confounded these stages by comparing brain responses evoked by novel and perceptually familiar famous faces. Here, we recorded EEG in two tasks in which subjects viewed two sets of faces that were equally perceptually familiar, but which had differing levels of associated person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Indeed, person-related semantic information enhances LPP amplitudes56. Recently, it has been further shown that biographical information can increase the LPP to computer-generated faces58. Although we did not provide participants with explicit biographical information, as a result of social inferences, the more realistic faces might be perceived as having a unique biographical identity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, person-related semantic information enhances LPP amplitudes56. Recently, it has been further shown that biographical information can increase the LPP to computer-generated faces58. Although we did not provide participants with explicit biographical information, as a result of social inferences, the more realistic faces might be perceived as having a unique biographical identity.…”
Section: Discussionmentioning
confidence: 89%
“…In this vein, manipulating perceived uniqueness or distinctiveness via shape or reflectance manipulations of initially non-distinctive real faces has been found to result in a larger late positivity as well as a better memory performance5455. Further, biographical information facilitates the processing of real faces at late ERP components5657, which has recently also been shown for realistic computer generated faces58. The combined evidence suggests that a unique identity, either pre-existing or ascribed, enhances processing particularly at late stages.…”
mentioning
confidence: 84%
“…To further investigate this possibility, we took advantage of electrophysiology and, specifically, event-related potentials (ERPs) to provide reliable neural markers capable of characterizing the neuropsychological profile of cognitive deficits (Rossini et al, 2020 ). As regards face processing, three main components have been found to correlate with face processing: the N170 (Bötzel et al, 1995 ; Bentin et al, 1996 ), the N250 (Schweinberger et al, 1995 , 2004 ), and the N400 components (Bentin and Deouell, 2000 ; Olivares et al, 2015 ; Taylor et al, 2016 ). Although the evidence is somewhat controversial, some studies have also suggested that the P100 may be sensitive to face processing, reflecting either a holistic face perception or differential low-level visual features between faces and other complex visual stimuli (Itier and Taylor, 2004 ; Rossion and Jacques, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike N170, the N250 and N400 components are modulated by personal familiarity (Bentin and Deouell, 2000 ; Webb et al, 2010 ; Olivares et al, 2015 ; Taylor et al, 2016 ). Therefore, they are both considered as indexes of face identification processing, albeit underpinning different aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies reporting early modulation for famous faces often involve stimulus selection based on subjects' previously assessed level of familiarity with various famous individuals (Huang et al, 2017). Lastly, studies using experimentally learned faces have also reported familiarity-dependent modulation of early components (Taylor et al, 2016). In all of these studies pre-activation of identity information can be regarded as defining the decisional space from which to-be-presented identities are drawn.…”
Section: Implications Beyond Visual Categorization Measured Behavioramentioning
confidence: 99%